Developing a customised learning design tool in support of curriculum design, professional development and institutional management within a South African military education context - van der Merwe, K. (South African Journal of Higher Education, 2024)
Learning design at tertiary level is a challenging and complex task with many aspects to take into consideration (Bennett, Lockyer, Agostinho 2018; Bower and Vlachopoulos 2018, 975; Bates, 2019). Learning design is identified as a core aspect of a tertiary educator’s role, but often, little guidance is given to educators on this topic. Changes in the higher education landscape also bring about questions about ideal learning design. With changing times that require institutions to introduce other models like blended and online learning, more pedagogical guidance might be necessary to advise lecturers on best practices in terms of module design (Kebritchi, Lipschuetz, and Santiague 2017). To aid learning design thinking and to make the pedagogic structure of the design apparent, Laurillard and Ljubojevic (2011) and others have suggested the use of a learning design tool or aid. A learning design tool is a means which can provide analytical support for lecturers to evaluate their own practices (Bower et al. 2011). This study looks at the creation of a customised learning design tool (CLDT) and discusses whether it can serve as an Electronic Performance Support System, which is a tool that can guide and assist users in their roles in the workplace. This case study canvassed the experiences and opinions of faculty members in Military Education on the use of this CLDT. The tool is designed to capture and depict various features of a module’s design. This study made use of design-based research which is a methodology requiring a phased approach and aims to influence practice. Inputs from the participants revealed the perceived value and benefits along with the necessary amendments needed for the tool.